European funding for environment and mobility - Macaluso, Michele; Guarracino, Giulio; Clemente, Nicola; Alves Acunzo, Nadijara (TeMA - Journal of Land Use, Mobility and Environment, 2012)
The "Guide on the European Programmes Funding for Energy, the Environment and Sustainable Mobility" is an overview of the most significant European funding programs (in the period 2007-2013) to promote the territory and mobility. The programs are aimed at financial measures and measures of environmental policy and governance, information and communication, product development, technical and research activities aimed at reducing CO2 emissions, reducing road congestion and pollution, for example by promoting media greener transport for the traffic of European goods. The total resources made ​​available by the programs is around 14 billion of euros, with financing arrangements and beneficiaries belonging to different geographical areas, including Italy and the Mediterranean. A peculiarity of these programs is to provide for notices (these calls) usually published on an annual/six monthly, which allow recipients to plan participation in the call later. These programs represent an opportunity for developing regions, such as the Southern Regions “Mezzogiorno”, who need more support to align with the average levels of growth in Europe. The complete guide, was presented by ANCE (National Association of Builders) and RENAEL (National Network of Local Energy Agencies), March 22, 2012, during EnergyMed (Exhibition and Conference on Renewable Sources and Energy Efficiency that held annually in Naples).